2011
DOI: 10.1002/14651858.cd007718.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Telehealthcare for chronic obstructive pulmonary disease

Abstract: Analysis 3.1. Comparison 3 Hospitalisations, Outcome 1 No. of patients with one or more hospitalisations in 12 months. Analysis 3.2. Comparison 3 Hospitalisations, Outcome 2 No. of patients entering a higher level of care over 6 months. Analysis 4.1. Comparison 4 Deaths over 12 months, Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 60 publications
1
126
0
4
Order By: Relevance
“…One review on chronic obstructive pulmonary disease (COPD) demonstrated the capacity of eHealth interventions to significantly reduce the number of patients with 1 or more emergency department visits or hospital admissions-due to exacerbation of pulmonary symptoms-over a 12-month period [23]. eHealth interventions did not significantly improve quality of life and all-cause mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One review on chronic obstructive pulmonary disease (COPD) demonstrated the capacity of eHealth interventions to significantly reduce the number of patients with 1 or more emergency department visits or hospital admissions-due to exacerbation of pulmonary symptoms-over a 12-month period [23]. eHealth interventions did not significantly improve quality of life and all-cause mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Among the systematic reviews and meta-analyses described in the current review are 4 high-quality Cochrane reviews [6,14,23,38]. Following the PRISMA Statement [10], the methodological quality of the other included papers was generally considered high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telehealth care has been shown to reduce hospitalizations in patients with chronic conditions such as asthma [6], chronic obstructive pulmonary disease [7], and heart failure [8,9]. Data also shows that telehealth care can achieve better blood pressure [17,18] and glycemic control [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have found telemedicine to be useful for monitoring chronic patients. Telecare in COPD appears to have a possible impact on the quality of life of patients and the number of times patients attend the emergency department and the hospital [12]. In our study, telemedicine was combined with face-to-face consultation once a month, which allowed us to see the patient in person and check the telemedicine equipment.…”
Section: Discussionmentioning
confidence: 99%